BASE-INDUCED C-5 EPIMERIZATION OF 4-METHYL-5-PHENYL OXAZOLIDINONES - CHIRAL AUXILIARIES DERIVED FROM NOREPHEDRINE AND NORPSEUDOEPHEDRINE - Davies, S; Doisneau, G (1993)
Treatment of cis- and trans-4-methyl-5-phenyl oxazolidinones 2 and 3 with excess butyllithium at 0°C results in C-5 epimerisation, via a common intermediate N,C-5-dianion, generating after protonation a 1:4 mixture of 2:3. © 1993.